Social determinants of health and postnatal wellbeing among women with type 2 diabetes in Thailand: An explanatory sequential mixed-methods study protocol - Ratchanok Phonyiam; Tippawan Srichalerm; Arissara Sawatpanich; Jantra Keawpugdee (PLoS ONE, 2026)
Introduction Type 2 diabetes mellitus affects pregnancy and can lead to maternal complications. Women affected by diabetes during pregnancy have ongoing physical, psychological, and social needs until birth preparation and after childbirth. The Social Determinants of Health (SDoH) can have a greater impact on health outcomes than healthcare services or personal lifestyle choices alone. To date, no study has explored how women with type 2 diabetes experience life after childbirth. To help close this knowledge gap, the proposed study aims to: 1) Culturally adapt and translate the Postnatal Well-being in Transition scale into Thai. 2) Quantitatively describe the SDoH and postnatal well-being during the diabetes transition among Thai women with T2DM. 3) Explore Thai women’s experiences regarding their SDoH, based on the mean scores of their postnatal well-being during the diabetes transition. And 4) Explore and analyze the impact of postnatal care on women with T2DM using a mixed-methods approach. Methods This is an explanatory sequential mixed-methods study protocol with two distinct phases. The first phase involves the translation of the study instrument, while the second phase focuses on data collection for the mixed-methods study. Data will be collected from 50 postnatal women with type 2 diabetes mellitus who have delivered a baby within the past six weeks. Participants will provide data on demographics, social determinants of health, and their postnatal well-being in transition. From this group, 12 women will be selected to participate in semi-structured, one-on-one interviews to gain a deeper understanding of their experiences. The study will use triangulation to integrate and validate the findings from both the quantitative and qualitative data sources. Ethics and dissemination Human Research Ethics Committee approval has been received from the Faculty of Medicine Ramathibodi Hospital, Mahidol University. The study findings will be reported in international journals.